2006
DOI: 10.1098/rspb.2005.3403
|View full text |Cite
|
Sign up to set email alerts
|

Fossilized soft tissues in a Silurian platyceratid gastropod

Abstract: Gastropod shells are common in the fossil record, but their fossil soft tissues are almost unknown, and have not been reported previously from the Palaeozoic. Here, we describe a Silurian (approx. 425 Myr) platyceratid gastropod from the Herefordshire Lagerstätte that preserves the oldest soft tissues yet reported from an undoubted crown-group mollusc. The digestive system is preserved in detail, and morphological data on the gonads, digestive gland, pedal muscle, radula, mouth and foot are also available. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Taken together, the interpretation of platyceratoid gastropods as the stem group of patellogastropods based on sharing of the same shell microstructure is in conflict with the pattern of their early shell ontogeny. Two years ago Sutton et al (2006) reported the discovery of an unusually well preserved gastropod with fossilized soft tissues from the Lower Silurian (Wenlock Series) Herefordshire Lagerstätte of England. This gastropod was assigned to the Platyceratidae on the basis of its simple subcircular aperture, trochiform shell and the absence of ornamentation.…”
Section: Platyceratids As a Stem Group Of Patellogastropodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Taken together, the interpretation of platyceratoid gastropods as the stem group of patellogastropods based on sharing of the same shell microstructure is in conflict with the pattern of their early shell ontogeny. Two years ago Sutton et al (2006) reported the discovery of an unusually well preserved gastropod with fossilized soft tissues from the Lower Silurian (Wenlock Series) Herefordshire Lagerstätte of England. This gastropod was assigned to the Platyceratidae on the basis of its simple subcircular aperture, trochiform shell and the absence of ornamentation.…”
Section: Platyceratids As a Stem Group Of Patellogastropodsmentioning
confidence: 99%
“…Its study has revealed detailed data on the digestive system as well as morphological data on the gonads, digestive gland, pedal muscle, radula, mouth and foot. According to Sutton et al (2006) the digestive system is the most informative phylogenetically of all the preserved soft-tissue characters. These anatomical data together with the absence of the operculum were interpreted as suggesting that platyceratids were symbiotic rather than predatory on their hosts.…”
Section: Platyceratids As a Stem Group Of Patellogastropodsmentioning
confidence: 99%
See 3 more Smart Citations